2009
DOI: 10.1111/j.1600-079x.2008.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates methamphetamine‐induced deactivation of the mammalian target of rapamycin signaling to induce autophagy in SK‐N‐SH cells

Abstract: Methamphetamine (METH) is a commonly abused drug that damages nerve terminals by causing reactive oxygen species (ROS) formation, apoptosis, and neuronal damage. Autophagy, a type of programmed cell death independent of apoptosis, is negatively regulated by the mammalian target of the rapamycin (mTOR) signaling pathway. It is not known, however, whether autophagy is involved in METH-induced neurotoxicity. Therefore, we investigated the effect of METH on autophagy and its upstream regulator, the mTOR signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 50 publications
6
54
0
Order By: Relevance
“…MLT has been shown to activate mTOR signaling and prevent ischemic brain injury and methamphetamine-induced neurotoxicity [36,37]. In this study, mTOR activity was decreased in livers subjected to I/R as demonstrated by decreased phosphorylation of mTOR, 4E-BP1 and 70S6K, while MLT treatment attenuated this decrease.…”
Section: Discussionmentioning
confidence: 52%
“…MLT has been shown to activate mTOR signaling and prevent ischemic brain injury and methamphetamine-induced neurotoxicity [36,37]. In this study, mTOR activity was decreased in livers subjected to I/R as demonstrated by decreased phosphorylation of mTOR, 4E-BP1 and 70S6K, while MLT treatment attenuated this decrease.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies suggest that chronic MA exposure decreases the phosphorylation of GSK3β in the ventral M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 tegmental area [12] and acute amphetamine treatment decreases the phosphorylation of Akt/GSK3 pathway in the striatum [13]. Besides, MA inhibits the activity of mTOR in both PC12 and SK-N-SH cells and the phosphorylation of mTOR is protective against MA induced neurotoxicity [14,15]. However, the effect of MA on Akt/ GSK3β/mTOR pathway in vitro has not been clearly determined yet.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have demonstrated that melatonin protected neuronal and glial cells in the central nervous system (CNS) after exposure to METH, both in vivo and in vitro, by reducing both inflammation cytokine production and the death signaling response [31][32][33][34][35][36][37][38][39]. However, the mechanism of inflammation in glial cells has not been extensively studied.…”
Section: Introductionmentioning
confidence: 97%